Strategi Guru Pendidikan Agama Islam Dalam Membentuk Akhlakul Karimah Peserta Didik Di MTs Nahdhatul Islam Mancang - Nadila Ananda Hidayat (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine the moral values instilled by PAI teachers and understand the strategies used by PAI teachers to shape the morals of students. Collecting this data the author uses a case study approach with qualitative research methods. The results of this discussion show that the moral formation carried out by PAI teachers is by maintaining cleanliness, caring for people and being able to take responsibility for what has been implemented. While the strategies used by PAI teachers to shape the morals of students are by giving examples to students, getting used to the dhuha prayer and midday prayers in congregation, and reading the Qur'an together so that students have noble character.